In-situ moisture conservation and nutrient management practices in fodder-sorghum (Sorghum bicolor) - Dass, Anchal; Singh, Anupama; Rana, K.S. (Annals of Agricultural Research, 2014)
Sorghum (Sorghum bicolor L. Moench) is the important source of dry-and green-fodder for a huge animal population, particularly in the arid-and semi-arid regions of India. It is cultivated under rain-fed environment on low fertility soils, and nutrient and moisture stress result in low productivity. Hence, a field experiment was conducted during rainy season of 2007-08 to study the effect of moisture conservation and nutrient management practices on sorghum growth and green-fodder yield, and soil moisture dynamics. The highest green fodder yield (26.64 t/ha) was recorded with mini-trenches (1 m × 0.2 m × 0.2 m) constructed at 2 m × 1 m interval followed by application of 8 t/ ha grasses/straw/tree-leaf mulch (24.84 t/ha). Use of 'Pusa hydrogel' (@ 5 kg/ha) enhanced sorghum fodder yield by 14.5% over control. Yield increment over control was 41.4% with mini-trenches and 31.9% with mulch application. In the nutrient management practices, the highest green-fodder yield (26.31 t/ha) was recorded from the plots treated with 5 t/ha farm-yard manure (FYM) + 10 t/ha green-leaf manuring (GLM) followed by GLM alone 10 t/ha (24.57 t/ha). The yield recorded with FYM + GLM was 46.5% higher over control (17.96 t/ha). Mini-trenches held on average 20% higher moisture content in soil profile over control. 'Pusa hydrogel' treated plots also showed higher soil moisture compared to control.